A new Ca15(PO4)2(SiO4)6:Eu2+ phosphor with green emission for use in n-UV based w-LEDs - Phuc Dang Huu; Phung Ton That; Phan Xuan Le (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
We have produced a novel phosphor using Eu2+, which is green in color coupled to Ca15(PO4)2(SiO4)6 (abbreviated as Ca15P2Si6) by deriving it structurally from α-Ca2SiO4 with a typical solit reaction method. Additionally, the decrease of Eu2+ concentration as well as heat endurance is being studied. 330 nm is the wavelength at which the substance is stimulated. At 491nm, it attain the greatest radiation energy  when filled with the ideal concentration of Eu2+, which is 0.5 mol%. The primary mechanism of concentration reduction is discovered to be the fast transfer of stimulation through exchanging coupling among stimulated Eu2+ ions. The heat activating power boundary has been determined to be 0.244 eV. Additionally, we assess the productivity of this matter by fabricating alight-emitting diodes (LED)with converted phosphor (pc-LED) and integrating a light-emitting diode (LED) with an InGaN-foundation near-ultraviolet and running it at currents between 50 mA and 300 mA. All of the efforts result in an optimal for pc-LED to be able to ecedewhite light-emitting diodes (WLED) implementations.